Strains of Drosophila melanogaster differ in alcohol tolerance. - Bokor, K.; Pecsenye, K. (Hereditas, 1997)
The influence of environmental ethanol on different fitness components and the larval activities of some enzymes were studied in three strains of Drosophila melanogaster. All three strains carried the AdhS-alphaGpdhF allele combination on their second chromosomes while they had unique allele combinations at the Odh and Aldox loci on their third chromosomes (strain 1: OdhS-AldoxF; strain 2: OdhF-AldoxS; strain 3: OdhS-AldoxS). Normal lines and exposure lines, kept on 5% ethanol supplemented medium for at least 20 generations, were established from each strain and the responses of the two lines to different ethanol concentrations were compared. Two survival components were estimated in the juvenile life history stages. In addition, the weights of the emerging adult males were measured at various concentrations of ethanol. The changes in the activities of two enzymes (ADH and alpha GPDH) were also surveyed in the larvae after the different ethanol treatments. Strain-specific differences were observed in the responses of all investigated traits to ethanol. OdhS-AldoxF larvae seemed to be more tolerant to ethanol than the larvae of the other two strains while the utilisation of ethanol as energy source appeared to be the least effective in this strain. Larvae of the exposure lines had significantly higher tolerance to ethanol, and the adult males were heavier, than the ones from the normal lines. The enzymatic responses of the two lines to the ethanol treatments were also different. ADH activity, fresh male weight, and pupa-to-adult survival seemed only to be associated under short-term exposure to ethanol. Ethanol tolerance appeared to be independent of the utilisation of ethanol in the larva-to-pupa stage.